If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -22 = 3(x + 2) Reorder the terms: -22 + 5x = 3(x + 2) Reorder the terms: -22 + 5x = 3(2 + x) -22 + 5x = (2 * 3 + x * 3) -22 + 5x = (6 + 3x) Solving -22 + 5x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -22 + 5x + -3x = 6 + 3x + -3x Combine like terms: 5x + -3x = 2x -22 + 2x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 -22 + 2x = 6 + 0 -22 + 2x = 6 Add '22' to each side of the equation. -22 + 22 + 2x = 6 + 22 Combine like terms: -22 + 22 = 0 0 + 2x = 6 + 22 2x = 6 + 22 Combine like terms: 6 + 22 = 28 2x = 28 Divide each side by '2'. x = 14 Simplifying x = 14
| 9+2z-3=6z+8-3z | | x*2/3=1/10 | | 7y-7-5y+2=0 | | 1/4=8^3x-7 | | 12y+6=6(6g+9) | | 2x/4=28 | | 2/5(x-1)x/2-5 | | 4b-3=-5 | | 32n=113 | | 2/5(x-1)x-2-5 | | 9+19n-7=9n+50-6n | | f(-x)=4x^2+5x+8 | | -3y-3=-1y-4 | | 3y-3=4y+1 | | 3(3+4x)-3=78 | | 5x+4=3x+8solving | | f(-x)=4x^2+dx+8 | | -7p+6p=-3 | | 695/x=139 | | 70+x=42+3x | | (5x^2-25)(2x^2-36)=0 | | 4xy=76 | | 9(x+3)+4=9x+9 | | (37x-15)+(44x-29)=360 | | (3y^1/4)^3 | | (37x-15)+(44x-29)=180 | | -7+15=-16 | | (3/4x-2/3)=(1/6) | | 3x^2+9x+4x+12= | | 2g+4(-8+3g)=1-g | | 3y-2(y-1)/6=-2 | | -1/5r=24/5 |